Presence of Candida tropicalis on Staphylococcus epidermidis Biofilms Facilitated Biofilm Production and Candida Dissemination: An Impact of Fungi on Bacterial Biofilms - Phuengmaung, Pornpimol; Panpetch, Wimonrat; Singkham-In, Uthaibhorn; Chatsuwan, Tanittha; Chirathaworn, Chintana; Leelahavanichkul, Asada (Frontiers in Cellular and Infection Microbiology, 2021)
While Staphylococcus epidermidis (SE) is a common cause of infections in implanted prostheses and other indwelling devices, partly due to the biofilm formation, Candida tropicalis (CT) is an emerging Candida spp. with a potent biofilm-producing property. Due to the possible co-existence between SE and CT infection in the same patient, characteristics of the polymicrobial biofilms from both organisms might be different from the biofilms of each organism. Then, the exploration on biofilms, from SE with or without CT, and an evaluation on L-cysteine (an antibiofilm against both bacteria and fungi) were performed. As such, Candida incubation in pre-formed SE biofilms (SE>CT) produced higher biofilms than the single- (SE or CT) or mixed-organism (SE+CT) biofilms as determined by crystal violet staining and fluorescent confocal images with z-stack thickness analysis. In parallel, SE>CT biofilms demonstrated higher expression of icaB and icaC than other groups at 20 and 24 h of the incubation suggesting an enhanced matrix polymerization and transportation, respectively. Although organism burdens (culture method) from single-microbial biofilms (SE or CT) were higher than multi-organism biofilms (SE+CT and SE>CT), macrophage cytokine responses (TNF-α and IL-6) against SE>CT biofilms were higher than other groups in parallel to the profound biofilms in SE>CT. Additionally, sepsis severity in mice with subcutaneously implanted SE>CT catheters was more severe than other groups as indicated by mortality rate, fungemia, serum cytokines (TNF-α and IL-6), kidney and liver injury. Although CT growth upon preformed SE-biofilms production, the biofilm structures were interfered during CT morphogenesis leading to the frailty of biofilm structure and resulting in the prominent candidemia. However, L-cysteine incubation together with the organisms in catheters reduced biofilms, microbial burdens, macrophage responses, and sepsis severity. In conclusion, SE>CT biofilms prominently induced biofilm-matrix, fungemia, macrophage responses and sepsis severity, whereas the microbial burdens were lower than the single-organism biofilms. All biofilms were attenuated by L-cysteine.